(untitled) (Research, Society and Development, 2022)
This research offers, through a bibliometric review, an overview of the latest publications on rural sanitation, aiming to assess the impact of scientific production on the subject and seek references for the formulation of management models. For this, publications from the Scopus database, the Bibliometrix tool and the VOSViewer software were used to perform evaluative and relational analyzes on the publications. This research showed the countries with the highest scientific production, the most cited, the most relevant journals, publications and works, and the most frequent keywords. In addition, the main works produced in the chosen theme were analyzed, noting that the development of management models for rural sanitation is little discussed, although relevant. Among the results, it is noteworthy that the countries with the highest scientific production on the subject are China, Brazil, the United States, the United Kingdom and India. Brazil appears in the list of countries with the most cited publications, indicating that national publications have a good impact factor.